Níveis de alérgenos inaláveis em veículos utilitários de transporte escolar em Uberlândia, MG - Justino, Caroline Morais (2005)
The allergen exposure is considered crucial for the development of allergies. The aim of this study was to measure mite (Der p 1 and Der f 1), dog (Can f 1) and cat (Fel d 1) allergens, in school transport vehicles. It was analized 163 seat dust samples from 60 vehicles, using ELISA tests. The Can f 1 allergen was the most frequent (geometric mean = 1.03 µg/g of dust). Only two (3.3%) vehicles showed levels of Der p 1 and two (3.3%) levels of Der f 1 at sensitizing levels, while 36 (60%) and 16 (26.7%) showed sensitizing levels of dog and cat allergens, respectively. Regarding to the vehicles from pet owners, in 20/32 (62.5%) vehicles from owners with dog at home, levels > 1 µg de Can f 1/g of dust were detected; however, there was no difference in Can f 1 levels in vehicles from owners that kept or not a dog at home, and whose owners that carried or not the animal inside the vehicle. On the other hand, in 15/28 (53.6%) vehicles from non-dog and 14/57 (24.5%) from non-cat owners, levels > 1 µg/g of dust were found. The dust cover used in seats interfered in the levels of mite and dog allergens, where allergen levels were lower in covered seats than uncovered seats. There was no statistical significant difference related to the age of the vehicles, the number of passengers carried in the car, and the vehicles were used part-time or not. We concluded that the school transport vehicles are reservoirs, especially of pet allergens, constituting vehicles for dispersion of these allergens for continuous contamination of the indoor environment.